Elevated Expression of Fractalkine (CX3CL1) and Fractalkine Receptor (CX3CR1) in the Dorsal Root Ganglia and Spinal Cord in Experimental Autoimmune Encephalomyelitis: Implications in Multiple Sclerosis-Induced Neuropathic Pain. (24th September 2013) - Zhu, Wenjun; Acosta, Crystal; MacNeil, Brian; Cortes, Claudia; Intrater, Howard; Gong, Yuewen; Namaka, Mike
Abstract : Multiple sclerosis (MS) is a central nervous system (CNS) disease resulting from a targeted autoimmune-mediated attack on myelin proteins in the CNS. The release of Th1 inflammatory mediators in the CNS activates macrophages, antibodies, and microglia resulting in myelin damage and the induction of neuropathic pain (NPP). Molecular signaling through fractalkine (CX3CL1), a nociceptive chemokine, via its receptor (CX3CR1) is thought to be associated with MS-induced NPP. An experimental autoimmune encephalomyelitis (EAE) model of MS was utilized to assess time dependent gene and protein expression changes of CX3CL1 and CX3CR1. Results revealed significant increases in mRNA and the protein expression of CX3CL1 and CX3CR1 in the dorsal root ganglia (DRG) and spinal cord (SC) 12 days after EAE induction compared to controls. This increased expression correlated with behavioural thermal sensory abnormalities consistent with NPP. Furthermore, this increased expression correlated with the peak neurological disability caused by EAE induction. This is the first study to identify CX3CL1 signaling through CX3CR1 via the DRG /SC anatomical connection that represents a critical pathway involved in NPP induction in an EAE model of MS.